2017
DOI: 10.1016/j.jjcc.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcome after treatment of severely calcified lesions with newer-generation drug-eluting stents in acute coronary syndromes

Abstract: In patients with ACS, treatment of severely calcified lesions with newer-generation DES was associated with an overall higher clinical event risk - related in particular to a higher TVR rate, while the risk of MI was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…Risk factors contributing to the development of coronary calcification include advanced age, diabetes, male sex and renal dysfunction. Coronary artery calcification, which can be found in 20–30% of all patients who undergo PCI, 2‐6 may result in a reduced vascular compliance and impair myocardial perfusion 1…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors contributing to the development of coronary calcification include advanced age, diabetes, male sex and renal dysfunction. Coronary artery calcification, which can be found in 20–30% of all patients who undergo PCI, 2‐6 may result in a reduced vascular compliance and impair myocardial perfusion 1…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed the 17-32% prevalence of moderate to severe coronary calcifications in this population [6,7]. The outcomes in this group are unfavorable, that is related to unsuccessful lesion preparation, stent delivery and expansion with subsequent procedure failure, target vessel failure, risk of restenosis, and stent thrombosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of lesion calcification was reported to be 19-32% in recent pooled analyses and metaanalyses of studies in patients with different clinical presentations. [14][15][16][17][18] Calcified lesions were slightly low, at 21.9%, in the present study, suggesting that the population of this study might have had a lower risk profile than previous studies, although both the RESET and NEXT had an allcomer study design. Nevertheless, worse clinical outcomes in patients with calcified lesions were observed in the present study, in which a large number of patients with moderate to severe calcification in real-world clinical practice were treated with G1-DES and G2-DES.…”
Section: Disclosuresmentioning
confidence: 54%
“…[27][28][29] Moreover, most all-comer randomized trials have not analyzed coronary calcification at an angiography core laboratory. Therefore, there have been only a few previous observational studies that have investigated the efficacy of DES in calcified lesions, 14,[16][17][18] and these have suggested that lesion calcification is associated with worse clinical outcome. The prevalence of lesion calcification was reported to be 19-32% in recent pooled analyses and metaanalyses of studies in patients with different clinical presentations.…”
Section: Disclosuresmentioning
confidence: 99%
See 1 more Smart Citation